Serum proteomics of mother-infant dyads carrying HLA-conferred type 1 diabetes risk - Bhosale, Santosh D.; Moulder, Robert; Suomi, Tomi; Ruohtula, Terhi; Honkanen, Jarno; Virtanen, Suvi M.; Ilonen, Jorma; Elo, Laura L.; Knip, Mikael; Lahesmaa, Riitta (Cell Press, 2025)
In-utero and dietary factors make important contributions towards health and development in early childhood. In this respect, serum proteomics of maturing infants can provide insights into studies of childhood diseases, which together with perinatal proteomes could reveal further biological perspectives. Accordingly, to determine differences between feeding groups and changes in infancy, serum proteomics analyses of mother-infant dyads with HLA-conferred susceptibility to type 1 diabetes (n = 22), weaned to either an extensively hydrolyzed or regular cow’s milk formula, were made. The LC-MS/MS analyses included samples from the beginning of third trimester, the time of delivery, 3 months postpartum, cord blood and samples from the infants at 3, 6, 9 and 12 months. Correlations between ranked protein intensities were detected within the dyads, together with perinatal and age-related changes. Comparison with intestinal permeability data revealed a number of significant correlations, which could merit further consideration in this context.